Hubungan Asupan Protein, Status Gizi Ibu Menyusui, dan Kandungan Protein pada Air Susu Ibu (ASI): Telaah Sistematik - Hapsari, Qori Chairunisa; Rahfiludin, Mohammad Zen; Pangestuti, Dina Rahayuning (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2021)
Latar belakang: Kandungan Air Susu Ibu (ASI) yang memiliki fungsi penting dalam mencegah morbiditas hingga mortalitas bayi adalah protein. Protein dalam ASI berfungsi dalam perkembangan, imunitas, antibakteri, antiinflamasi, dan antiinfeksi. Kandungan protein dalam ASI dipengaruhi oleh beberapa hal yaitu asupan protein ibu dan status gizi ibu menyusui. Sumber protein yang dikonsumsi ibu menyusui akan diserap oleh tubuh dan kemudian dialirkan ke dalam kantung ASI untuk selanjutnya digunakan dalam pembentukan protein ASI. Ibu yang memiliki status gizi baik akan menyerap asupan protein dengan lebih baik sehingga kandungan protein dalam ASI lebih optimal. Tujuan dari penelitian studi literatur ini adalah untuk mengetahui apakah terdapat hubungan asupan protein, status gizi ibu menyusui dan kandungan protein yang terdapat dalam ASI.Metode: Jenis penelitian yang dilakukan adalah studi literatur menggunakan sumber data yang berasal dari hasil pencarian pada database online antara lain SCOPUS, Science Direct, Google Scholar, Proquest, dan Portal Garuda yang memuat jurnal nasional dan internasional terakreditasi. Â Hasil: Pencarian artikel berdasarkan kata kunci didapatkan sebanyak 7389 artikel. Hasil akhir didapat 18 artikel yang memenuhi syarat untuk direview. Terdapat 9 artikel terkait asupan protein ibu menyusui terhadap kandungan protein ASI dan 13 artikel terkait status gizi ibu menyusui terhadap kandungan protein ASI.Simpulan: Terdapat 4 dari total 9 artikel menyatakan adanya hubungan antara asupan protein dan kandungan protein ASI. Terdapat 8 dari 13 artikel menyatakan ada hubungan antara status gizi ibu menyusui dan kandungan protein ASI. Asupan protein memiliki hubungan secara tidak langsung terhadap kandungan protein pada ASI dikarenakan penyerapan asupan protein pada ibu dan produksi protein ASI dipengaruhi oleh status gizi ibu serta hormon. Status gizi ibu menyusui memiliki hubungan secara langsung terhadap kandungan protein pada ASI. Ibu yang memiliki status gizi baik akan menyerap protein dari makanan dengan lebih optimal serta akan menghasilkan ASI dengan kandungan protein yang optimal.Kata kunci: Ibu Menyusui; ASI, Protein; Asupan Protein; Status GiziÂ ABSTRACT Title: Relationship Between Protein Intake, Nutritional Status of Breastfeeding Mothers and Protein Content in Breast Milk: Literature ReviewBackground: The content of human milk (ASI) that has an important function to preventing morbidity and mortality for infant is protein. Protein in human milk has many functions such as development, immunity, antibacterial, anti-inflammatory, and anti-infective. The protein content in breast milk is influenced by several things, there are maternal protein intake and nutritional status of breastfeeding mothers. The source of protein consumed by breastfeeding mothers will be absorbed by the body and then flowed into the breast milk bag for further use in the formation of breast milk protein. Mothers who have good nutritional status will absorb protein intake better so that the protein content in breast milk are being optimal. The purpose of this literature study was to determine whether there was a relationship between protein intake, nutritional status of breastfeeding mothers and protein content in breast milk.Method: The type of research is a literature study because researcher using data sources from online databases, including SCOPUS, Science Direct, Google Scholar, Proquest, and the Garuda Portal which contains accredited national and international journals.Result: There are found 7389 articles based on keywords. The final results obtained 18 articles that meet the requirements for review. There are 9 articles related to protein intake of breastfeeding mothers on protein content of breast milk, 13 articles related to nutritional status of breastfeeding mothers on protein content of breast milk, and 4 articles regarding protein intake and nutritional status of breastfeeding mothers on protein content of breast milk.Conclusion: There are 4 out of a total of 9 articles stating a relationship between protein intake and protein content of breast milk. There are 8 out of 13 articles stating that there is a relationship between the nutritional status of breastfeeding mothers and the protein content of breast milk. There are 2 out of 4 articles stated that there was a relationship between protein intake of breastfeeding mothers and protein content in breast milk, and there was no relationship between nutritional status of breastfeeding mothers and protein content in breast milk. Protein intake has an indirect relationship to protein content in breast milk because the absorption of protein intake in the mother and protein production in breast milk is influenced by the nutritional status of the mother and hormones. The nutritional status of breastfeeding mothers has a direct relationship to the protein content of breast milk. Mothers who have good nutritional status will absorb protein from food optimally and will produce breast milk with optimal protein content.Keywords: Breastfeeding Mother; Human Milk; Protein; Protein Intake; Nutritional Status